143 A Youth-Led Digital Education Intervention to Improve Blood Pressure for Adults Who Present to the Emergency Department with Hypertension. (April 2022) - Heinert, Sara; Escalante, Victoria; Chen, Annie; Penugonda, Ananya; Crabtree, Benjamin; Greene, Kathryn; Heckman, Carolyn; Ohman-Strickland, Pamela; Hudson, Shawna
Abstract : OBJECTIVES/GOALS: To describe a study to develop, test, and collect implementation data on a youth-led hypertension (HTN) education digital intervention that acts as an electronic tool to guide youth through learning and then teaching adults on how to achieve better HTN control. Adults with uncontrolled HTN are recruited from a New Jersey emergency department (ED). METHODS/STUDY POPULATION: Adults with HTN and youth (15-18 years) participate in a remote user-centered design session focus group to provide input in the development of the youth-led HTN education digital intervention. 100 adult ED patients with uncontrolled HTN (blood pressure (BP) â‰¥130/80 mm Hg) who live with a youth (15-18 years) and the youth themselves are recruited for a randomized control trial (RCT). The adult-youth dyad is randomized to one of two arms, each a 6-week program with youth earning a digital badge: 1) intervention- youth-led HTN education with the adult, or 2) control- youth learn life skills (such as job readiness/resume building). Implementation metrics are collected through a post-intervention survey and qualitative interviews on the digital badge intervention including acceptability, feasibility, and fidelity. RESULTS/ANTICIPATED RESULTS: We completed two youth focus groups (total of 8 participants) and data collection is ongoing. Youth have shown great interest in the intervention prototype and thought their peers would find it acceptable. They suggested additions to nutrition education activities, such as adding a sodium tracker and examples of high sodium foods. For the RCT, the primary study outcome is adult BP change (from baseline to 1 week and 2-months post-intervention), with secondary outcomes of HTN knowledge and youth self-efficacy. We anticipate that intervention arm adults will have a more significant decrease in BP than control arm adults. We also expect that HTN knowledge and youth self-efficacy will be higher for the intervention arm. Implementation data collected will allow for improvements to future renditions of the intervention. DISCUSSION/SIGNIFICANCE: Bringing health education home while simultaneously empowering youth is an innovative technology-driven model for improving BP for patients with uncontrolled HTN who may lack access to care. Outcomes of this project will result in a scalable and easily adoptable model to reach an otherwise difficult to reach adult population.